2020
DOI: 10.1186/s12883-020-1626-6
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal blood pressure circadian rhythms are relevant to cerebral infarction and Leukoaraiosis in hypertensive patients

Abstract: Background: To investigate the relationships between blood pressure (BP) circadian rhythms and acute cerebral infarction (ACI), silent cerebral infarction (SCI) and the severity of leukoaraiosis in hypertensive patients. Methods: A retrospective case-control study was performed among hypertensive patients with 24-h ambulatory blood pressure monitoring (ABPM) and cranial magnetic resonance imaging (MRI). Results: A total of 1267 patients were enrolled. Lower nocturnal blood pressure (BP) decreases were observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 45 publications
0
11
0
2
Order By: Relevance
“…A recent study based on the Rotterdam study demonstrated that increased visit-to-visit BPV led to subclinical brain microstructure alterations including CSVD (Ma et al, 2020). In contrast, our previous study found that abnormal blood pressure circadian rhythms correlated with cerebral infarction and leukoaraiosis (Yang et al, 2020). However, how abnormal BPV promotes cerebral structure remains to be clarified (Iadecola and Parikh, 2020).…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…A recent study based on the Rotterdam study demonstrated that increased visit-to-visit BPV led to subclinical brain microstructure alterations including CSVD (Ma et al, 2020). In contrast, our previous study found that abnormal blood pressure circadian rhythms correlated with cerebral infarction and leukoaraiosis (Yang et al, 2020). However, how abnormal BPV promotes cerebral structure remains to be clarified (Iadecola and Parikh, 2020).…”
Section: Discussionmentioning
confidence: 76%
“…Categorical data were expressed as frequencies and percentages and were compared using chi-square tests or Fisher’s exact tests, when appropriate. Variables with P < 0.1 and variables relevant to our research (lacunes, EPVS, brain atrophy, WMH, cSS, and BPV subtype) ( Yang et al, 2020 ; Xu et al, 2021 ) were included in a subsequent multivariate logistic regression to identify independent predictors. When exploring predictors for MACCE, each CSVD marker and total CSVD marker numbers were included in two distinct models to avoid collinearity because they were mutually closely correlated.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pasien hipertensi, terutama pasien hipertensi kronis, terjadi penebalan dinding bagian dalam dan degenerasi hialin pada arteriol intrakranial dan arteri perforasi dalam. Karena kurangnya arteri perforasi dalam dan sirkulasi kolateral, materi putih terluka, dan kemudian terjadi leukoaraiosis (Yang et al, 2020). Hipertensi sangat terkait dengan penyakit materi putih dan mungkin merupakan faktor risiko paling penting yang dapat dimodifikasi.…”
Section: Metodologiunclassified
“…Cerebral infarction, a common disease affecting the nervous system, has evolved into the top three lethal diseases causing mortality [ 1 ]. Despite the risk of stroke dropping by 25% till 2010 as medical technologies and methods advanced, the rate of disability remains on the rise even over 80%, struck by sequelae, namely, motor, sensory, and cognitive disorders, which become a heavy burden carried upon the shoulders of patients, their families, and society [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%